INTERVENTION OF GROUP-BASED COGNITIVE BEHAVIORAL THERAPY (CBT) TO REDUCE ANXIETY AMONG CARDIAC PATIENTS: A RANDOMIZED CONTROLLED STUDY (Contemporary Journal of Social Science Review, 2025)
The current research aims to investigate the effectiveness of group-based CBT in reducing anxiety among cardiac patients in Karachi. Research design of Randomized controlled trial (RCT) to compare outcomes between an intervention group receiving group-based CBT and a control group research design was used. A non-probability purposive sampling technique was used to approach diagnosed cardiac patients (N=40) with an age range of 20-70 years with mean age group of 3.52 (± SD=0.93). The data was collected through the Generalized Anxiety Scale (Robert L. Spitzer et al., 2006). The intervention included a 12-session plan following the theoretical framework of Dan DeSena for anxiety reduction through CBT. Findings of paired sample t-test highlighted a statistically significant decrease in the level of anxiety at post-intervention as compared to pre-intervention (M = 15.9, SD = 2.46 at pre-test; M = 9.9, SD = 2.57 at post-test; t(19) = 10.1, p < .001), is evident in individuals who have taken 12 sessions of group-based cognitive behavioral therapy interventions, indicating that group CBT is effective in alleviating symptoms of anxiety in cardiac patients (Aghaei, et al., 2015). These findings have significant clinical and research implications.